Analysis of competency profile for vocational graduates - Haryadi, Rudi; Abdullah, Ade Gafar; Widiaty, Isma (Jurnal Penelitian Pendidikan, 2024)
Learning activity at Vocational High Schools (VHS) is held to equip students with competencies according to the skill program they have chosen and to meet job competency expectations from industry. This study presents data on the process and expectations of graduate competence from the point of view of learning in VHS which was conducted through a survey of 406 respondents with the dominance of learning instructors in a number of VHS that spread across Indonesia. The survey was conducted online containing the learning process, competencies, job opportunities, also career paths. The results of this study indicate that learning at VHS has been carried out oriented towards work demands in accordance with the field of expertise, but the work competencies assessed by the school as having met the work demands have not been fully recognized by the workplace, so that a form of job training is needed to provide strengthening and recognition of competence by industry in the form of certification, work activities and culture, recruitment and monitoring of the implementation of training results to see the development of career paths. The large number of graduates who are looking for work and efforts to fulfill work competencies after they finish learning at school provide recommendations for job training to be carried out during the transition period after completing learning at VHS before the start of work activities in industry.
Keywords: career paths; hs learning; job competencies; vhs graduates